PENERAPAN GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING (MFCA)TERHADAP SUSTAINABLE DEVELOPMENT - Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2018)
This study aims to determine whether there is a relationship and influence between Green Accounting Implementation, Material Flow Cost Accounting (MFCA) to Sustainabale Development and Resource Eficiency as moderation. The sample used consists of five cement companies listed in Indonesian Cement Association in 2017. The method used in this research is purposive sampling. To measure Green Accounting Implementation, Material Flow Cost Accounting (MFCA) on Sustainabale Development and Resource Eficiency as moderation is used multiple analysis. The results show that Green Accounting Implementation, Material Flow Cost Accounting (MFCA) has a positive effect on Sustainabale Development and Resource Eficiency as moderation. Resource Efficiency strengthens the Implementation of Green Accounting and Material Flow Cost Accounting (MFCA) against Suistainabale development (SDv).